Prospective Salmonella Enteritidis surveillance and outbreak detection using whole genome sequencing, Minnesota 2015–2017. (16th June 2020) - Rounds, J. M.; Taylor, A. J.; Eikmeier, D.; Nichols, M. M.; Lappi, V.; Wirth, S. E.; Boxrud, D. J.; Smith, K. E.; Medus, C.
Abstract: Clusters of Salmonella Enteritidis cases were identified by the Minnesota Department of Health using both pulsed-field gel electrophoresis (PFGE) and whole genome sequencing (WGS) single nucleotide polymorphism analysis from 1 January 2015 through 31 December 2017. The median turnaround time for obtaining WGS results was 11 days longer than for PFGE (12 vs. 1 day). WGS analysis more than doubled the number of clusters compared to PFGE analysis, but reduced the total number of cases included in clusters by 34%. The median cluster size was two cases for WGS compared to four for PFGE, and the median duration of WGS clusters was 27 days shorter than PFGE clusters. While the percentage of PFGE clusters with a confirmed source (46%) was higher than WGS clusters (32%), a higher percentage of cases in clusters that were confirmed as outbreaks reported the vehicle or exposure of interest for WGS (78%) than PFGE (46%). WGS cluster size was a significant predictor of an outbreak source being confirmed. WGS data have enhanced S . Enteritidis cluster investigations in Minnesota by improving the specificity of cluster case definitions and has become an integral part of the S . Enteritidis surveillance process.